Non-pharmacological Therapies for Tic Disorders in Children and Adolescents: Methods, Advantages, and Limitations - Yongmei, Hou (Medical Science: Trends and Innovations Vol. 6, 2025)
Background: Non-pharmacological therapies are an important method for the treatment of tic disorders in children and adolescents, characterized by significant efficacy, wide applicability, and few side effects. To some extent, they complement the deficiencies of pharmacotherapy, yet they have not received sufficient attention and application. Objective: The objective of the study is to understand the main methods, advantages, and disadvantages of non-pharmacological therapies for tic disorders in children and adolescents. Methods: A literature search was conducted using the keywords [“children” or “adolescents” or “youths”] and [“tic disorders” or “Tourette syndrome”] in PubMed, Web of Science, CINAHL Plus, Scopus, Embase, PsycINFO, and CNKI over the past 25 years. Results: A total of 58 papers were included. Previous literature shows that non-pharmacological therapies can effectively reduce tic symptoms in children and adolescents, alleviate their negative emotions such as depression and anxiety, improve their school attendance and self-esteem, promote their social development, and improve their quality of life. However, most non-pharmacological therapies lack rigorous operational guidelines and exploration of long-term efficacy. Conclusion: Non-pharmacological therapies provide new ideas for the treatment of tic disorders in children and adolescents. Establishing unified operational guidelines, clarifying long-term efficacy, and strengthening the combined application of non-pharmacological and pharmacologic therapies are important directions for future research.